A case report of tongue metastasis from lung squamous cell carcinoma and literature review. Issue 40 (October 2017) - Cheng, Xiaolong; Hu, Zhenli; Han, Yipin; Bai, Chong
Abstract: Rationale: Tongue metastasis from lung cancer is extremely rare, and the prognosis of these patients is rather poor. Patient concers: A 56-year-old man was found a 4-cm cavity lesion in the left upper lobe, which was initially misdiagnosed as tuberculosis. Diagnoses: A case of lung squamous cell carcinoma that metastasized to the base of a patient's tongue. Intervations: We send the biopsy of the lung and the tongue lesions for gene sequencing. Outcomes: He received systemic chemotherapy, but continued to have pain at the base of his tongue and died 7 months later. Lessons: From sequencing data, mutations in KRAS proto-oncogene, GTPase (KRAS), phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), and tumor protein p53 (TP53) were found in the tumor biopsy of the patient. All of these were indicators of poor prognosis.